Functional Notation

advertisement
Lesson 5.2 (PART 2)
Functional Notation
An equation that is a function may
be expressed using functional
notation.
The notation f(x) (read “f of (x)”)
represents the variable y.
Functional Notation Cont’d
Example:
y = 2x + 6 can be written as f(x) = 2x + 6.
Given the equation y = 2x + 6, evaluate when x = 3.
y = 2(3) + 6
y = 12
Functional Notation Con’t
For the function f(x) = 2x + 6, the notation f(3)
means that the variable x is replaced with the
value of 3.
f(x) = 2x + 6
f(3) = 2(3) + 6
f(3) = 12
Evaluating Functions
Given f(x) = 4x + 8, find each:
1. f(2) = 4(2) + 8
= 16
2. f(a +1) = 4(a + 1) + 8
= 4a + 4 + 8
= 4a + 12
3. f(4a)
= 4(-4a) + 8
= -16a+ 8
Determine the value of x when
given f(x).
Given f(x) = 4x + 8, determine x when:
f(x) = 2
f (x) = -1
Evaluating More Functions
If f(x) = 3x  1, and g(x) = 5x + 3, find each:
1.
f(2) + g(3) = [3(2) -1] + [5(3) + 3]
= 6 - 1 + 15 + 3
= 23
2.
f(4) - g(-2) = [3(4) - 1] - [5(-2) + 3]
= 11 - (-7)
= 18
3.
3f(1) + 2g(2) = 3[3(1) - 1] + 2[5(2) + 3]
= 6 + 26
= 32